A Dendrogeomorphological Study of the Local Effect of Climate Change - L. A., Datri; R., Maddio; A. M., Faggi; L. A., Gallo (European Scientific Journal, ESJ, 2017)
The climatic and environmental conditions of Patagonia changed substantially after 1850 and after the mid-1970s decade. The impact of these changes is being observed in the new configuration of rivers and their riverine vegetation. The objective of this work is to integrate dendrogeomorphological techniques to the mapping and modeling of the recent distribution of vegetation of the riverine landscape, as an indicator of the local effect of climate change.The hydrological regime and the evolution of riparian vegetation at the confluence of the Cuyin Manzano and Traful Rivers were synchronized using the data obtained from 34 samples of plots of 6x6 meters. The plots were adjusted to the pixel resolution of two SPOT 7 satellite images (flood and dryness), concentric to an area of 18x18 meters, in order to validate a supervised classification of vegetation, belonging to different fluvial geoforms. In the plots with woody vegetation two trees corresponding to one or two age classes characteristic of the stands were drilled. The results indicate that, in agreement with global and Patagonia climate change estimates, there is a slight tendency of change in the flood and drought regime, with decreases in mean annual minimum flows and a period of drought in the last six years. The most outstanding result of our study indicates that the change of the hydrological regime implies a slight reduction of the average minimum flows, without this entailing a modification of the regime of flood pulses that in some cases are very extreme. This situation has a marked incidence in the fact that the woody vegetation colonizes new substrates and emerged landforms, while it is affected by frequent and intense flood events, with a change of the compositions and distribution of the vegetation.